Role of Job Satisfaction as Mediator between the Causes and Level of Burnout: Case Study on Yemeni Healthcare Employees - Al-Maqdam, Nail Abdo Ali Yahya; Hazbar, Abdulmalek H. A; Ali, Faisal A. M; Al-Mansari, Ali Abdulqawi (مجلة العلوم التربوية والدراسات الإنسانية سلسلة الآداب والعلوم التربوية والإنسانية والتطبيقية, 2025)
Occupational burnout among healthcare professionals can have severe consequences on their health, the quality of patient care, and the overall performance of the healthcare system, especially during pandemics like COVID-(19). The aim of this study was to determine the prevalence of occupational burnout syndrome among healthcare providers working at Al-Thawra and Al-Jumhuri hospitals in Taiz, Yemen, and to assess the direct impact of work reference, social relationships, workload, and lack of support on occupational burnout syndrome. Additionally, the study measured the indirect effect through the job satisfaction variable. A quantitative descriptive approach was used, and data were collected using the Maslach Burnout Inventory (MBI) to assess burnout and the Minnesota Satisfaction Questionnaire (MSQ) to evaluate job satisfaction, from a sample of 181 employees at the two hospitals. Data were analyzed using Partial Least Squares Structural Equation Modeling (SMART PLS 4). The results revealed that sources of burnout were at a high level, while the level of burnout syndrome occurrence was moderate. It was found that lack of support, work reference, and workload had direct effects on burnout syndrome, with coefficients of (0.45%), (0.17%), and 0.16%, respectively. However, social relationships did not have a statistically significant direct impact on burnout syndrome. The study also indicated that job satisfaction plays a mediating role in the relationship between social burnout sources and occupational burnout syndrome. Furthermore, demographic factors showed no statistically significant impact on the occurrence of burnout syndrome. The study recommends appropriate interventions by implementing preventive measures and necessary programs to prevent occupational burnout syndrome, along with regular screenings for early detection and treatment of burnout syndrome.